Differences in Maturation Status and Immune Phenotypes of Circulating Helios+ and Helios− Tregs and Their Disrupted Correlations With Monocyte Subsets in Autoantibody-Positive T1D Individuals - Zhang, Yuyue; Zhang, Jie; Shi, Yun; Shen, Min; Lv, Hui; Chen, Shu; Feng, Yingjie; Chen, Heng; Xu, Xinyu; Yang, Tao; Xu, Kuanfeng (Frontiers in Immunology, 2021)
CD4 Tregs are involved in the regulation of various autoimmune diseases but believed to be highly heterogeneous. Studies have indicated that Helios controls a distinct subset of functional Tregs. However, the immunological changes in circulating Helios+ and Helios− Tregs are not fully explored in type 1 diabetes (T1D). Here, we elucidated the differences in maturation status and immune regulatory phenotypes of Helios+ and Helios− Tregs and their correlations with monocyte subsets in T1D individuals. As CD25−/low FOXP3+ Tregs also represent a subset of functional Tregs, we defined Tregs as FOXP3+CD127−/low and examined circulating Helios+ and Helios− Treg subpopulations in 68 autoantibody-positive T1D individuals and 68 age-matched healthy controls. We found that expression of both FOXP3 and CTLA4 diminished in Helios− Tregs, while the proportion of CD25−/low Tregs increased in Helios+ Tregs of T1D individuals. Although the frequencies of neither Helios+ nor Helios− Tregs were affected by investigated T1D genetic risk loci, Helios+ Tregs correlated with age at T1D diagnosis negatively and disease duration positively. Moreover, the negative correlation between central and effector memory proportions of Helios+ Tregs in healthy controls was disrupted in T1D individuals. Finally, regulatory non-classical and intermediate monocytes also decreased in T1D individuals, and positive correlations between these regulatory monocytes and Helios+/Helios− Treg subsets in healthy controls disappeared in T1D individuals. In conclusion, we demonstrated the alternations in maturation status and immune phenotypes in Helios+ and Helios− Treg subsets and revealed the missing association between these Treg subsets and monocyte subsets in T1D individuals, which might point out another option for elucidating T1D mechanisms.